Sheep polyclonal antibody to map Haemonchus contortus mimotopes using phage display library - Buzatti,Andréia (2018)
Abstract The aim of this study was to evaluate phage display technology for mapping Haemonchus contortus mimotopes. We screened the PhD-7 Phage Display Peptide Library Kit with a sheep polyclonal antibody against H. contortus. After four rounds of selection, 50 phage peptide clones were selected by biopanning and sequenced. Two clones displaying peptide mimotopes of H. contortus proteins were chosen for sheep immunization: clone 6 - mimotope of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and clone 17 - mimotope of a disorganized muscle family member (Dim 1). Twelve sheep were allocated into 3 groups of 4 animals as follow: G1: control group; G2/GAPDH: immunized with clone 6; and G3/Dim1: immunized with clone 17. Four immunizations were performed at intervals of seven days (0, 7, 14, and 21 days). On day 28 post initial vaccination, all groups were orally challenged with 2500 H. contortus infective larvae. The mimotope peptides selected by phage display were recognized by IgG from sheep naturaly infected with H. contortus. The immunization protocol showed an increasein IgG anti-M13 phage titers, but no effect was observed in IgG-specific for the anti-mimotope peptides. This is the first report of successful use of a phage display library for the identification of mimotopes of H. contortus proteins.